Originality of Thinking among University Students - Abdul Wahid, Bilal Sabah; Hamid al-Dulaimi, Qusay Hamid (Journal of Tikrit University for Humanities, 2023)
The primary objective of the present study is to ascertain the level of originality in thinking shown by university students. Additionally, this research seeks to examine the possible influence of three variables: gender (male vs. female), specialty (scientific vs. human), and academic stage (third and fourth years). The two researchers devised a test to assess the level of originality in thinking, a crucial component of the fundamental criteria for contemporary research. The exam consisted of 20 questions in its first version. The final version of the study comprises 20 items. The researchers collected data and performed statistical analyses, including the t-test, Pearson’s correlation coefficient, and triple variance analysis. Based on these analyses, the researchers determined that the level of original thinking among university students is satisfactory. Consequently, the researchers formulated several recommendations and proposals in response to these findings